2022
DOI: 10.3390/math10224171
|View full text |Cite
|
Sign up to set email alerts
|

Novel Soliton Solutions of the Fractional Riemann Wave Equation via a Mathematical Method

Abstract: The Riemann wave equation is an intriguing nonlinear equation in the areas of tsunamis and tidal waves in oceans, electromagnetic waves in transmission lines, magnetic and ionic sound radiations in plasmas, static and uniform media, etc. In this innovative research, the analytical solutions of the fractional Riemann wave equation with a conformable derivative were retrieved as a special case, and broad-spectrum solutions with unknown parameters were established with the improved (G’/G)-expansion method. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Due to the significance of RWE, numerous authors have obtained the solution of the Riemann wave equation by employing various methods, including generalized ¢ G G ( )-expansion method [16], new extended direct algebraic method [17], generalized Kudryashov method [18], extended tanh function technique [19], Wronskian method [20], generalized exponential rational function approach [21], and modified q -u exp( ( ))-function method [22]. While, the solutions of FRWE with conformable fractional derivative have acquired by improved ¢ G G ( )-expansion method [23]. Moreover, the stochastic Riemann wave equation was considered by Mohammed et al [24] and they found its solutions by using the extended tanh-coth method and the mapping method.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significance of RWE, numerous authors have obtained the solution of the Riemann wave equation by employing various methods, including generalized ¢ G G ( )-expansion method [16], new extended direct algebraic method [17], generalized Kudryashov method [18], extended tanh function technique [19], Wronskian method [20], generalized exponential rational function approach [21], and modified q -u exp( ( ))-function method [22]. While, the solutions of FRWE with conformable fractional derivative have acquired by improved ¢ G G ( )-expansion method [23]. Moreover, the stochastic Riemann wave equation was considered by Mohammed et al [24] and they found its solutions by using the extended tanh-coth method and the mapping method.…”
Section: Introductionmentioning
confidence: 99%